Isu 3 Periode Masa Jabatan Presiden Dalam Sudut Pandang Demokrasi - riady riady; Syugiarto Syugiarto (Universitas 17 Agustus 1945 Jakarta, 2022)
This study aims to see whether the president can serve his term of office for 3 periods (15 years) from a democratic point of view. This research itself uses literature study as the basis for data collection. The theory of democracy is used as a reference to see the term of office of the president for 3 periods from a democratic point of view, and also whether it will harm democracy itself or not. The results show that the president can hold office for 3 periods (15 years) if Article 7 of the 1945 Constitution of the Republic of Indonesia is amended again. In addition, if the majority of people want the president to serve more than 2 periods (10 years), then this will not injury democracy at all. This is because people want it. However, if we refer to the reasons why Article 7 of the 1945 Constitution was amended in 1999 (which is to reflect democracy and leadership regeneration) and there are rejections from some parties who do not want the presidential term of leadership more than 2 periods, it will show that the government is disobedient to regulations that have been mutually agreed upon and do not pay attention to the wishes of some people who reject it.